Dysphagia-optimised Intensity-modulated Radiotherapy Techniques in Pharyngeal Cancers: Is Anyone Going to Swallow it?. Issue 7 (July 2017) - Petkar, I.; Bhide, S.; Newbold, K.; Harrington, K.; Nutting, C.
Abstract: Dysphagia after primary chemoradiotherapy or radiation alone in pharyngeal cancers can have a devastating impact on a patient's physical, social and emotional state. Establishing and validating efficient dysphagia-optimised radiotherapy techniques is, therefore, of paramount importance in an era where health-related quality of life measures are increasingly influential determinants of curative management strategies, particularly as the incidence of good prognosis, human papillomavirus-driven pharyngeal cancer in younger patients continues to rise. The preferential sparing achievable with intensity-modulated radiotherapy (IMRT) of key swallowing structures implicated in post-radiation dysfunction, such as the pharyngeal constrictor muscles (PCM), has generated significant research into toxicity-mitigating strategies. The lack of randomised evidence, however, means that there remains uncertainty about the true clinical benefits of the dosimetric gains offered by technological advances in radiotherapy. As a result, we feel that IMRT techniques that spare PCM cannot be incorporated into routine practice. In this review, we discuss the swallowing structures responsible for functional impairment, analyse the studies that have explored the dose–response relationship between these critical structures and late dysphagia, and consider the merits of reported dysphagia-optimised IMRT (Do-IMRT) approaches, thus far. Finally, we discuss the dysphagia/aspiration-related structures (DARS) study (ISRCTN 25458988), which is the first phase III randomised controlled trial designed to investigate the impact of swallow-sparing strategies on improving long-term function. To maximise patient benefits, improvements in radiation delivery will need to integrate with novel treatment paradigms and comprehensive rehabilitation strategies to eventually provide a patient-centric, personalised treatment plan.